A Force for Law and Order. Issue 3 (7th October 2016) - Herndon, James S.
Abstract : Much of police psychology over the past 50 years or so has been clinically focused. The role and function of the industrial–organizational (I-O) psychologist within the context of law enforcement was highlighted by Lefkowitz (1977 ), and in the years since, the contributions of I-O psychology applied to law enforcement issues have become increasingly valued. It is, therefore, appreciated that Ruggs et al. (2016 ) offer suggestions for how I-O psychologists might get involved in addressing some of the current hot spots in police work.